2018
DOI: 10.1038/s41598-018-24875-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between atrial fibrillation, atrial enlargement, and left ventricular geometric remodeling

Abstract: This study investigated the relationship between atrial fibrillation (AF) and left ventricular (LV) geometric patterns in a hospital-based population in Japan. We retrospectively analyzed 4444 patients who had undergone simultaneous scheduled transthoracic echocardiography (TTE) and electrocardiography during 2013. A total of 430 patients who had findings of previous myocardial infarctions (n = 419) and without the data on body surface area (n = 11) were excluded from the study. We calculated the LV mass index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 31 publications
7
76
0
8
Order By: Relevance
“…These findings suggest an association between AF and WMHs. Moreover, they agree with previous studies reporting an association between left ventricle remodelling and AF [17]. No significant associations were found for brain ventricles volume, WMHs volume and age.…”
Section: Bootstrap Distribution Of Correlation Between Cardiac Paramesupporting
confidence: 92%
“…These findings suggest an association between AF and WMHs. Moreover, they agree with previous studies reporting an association between left ventricle remodelling and AF [17]. No significant associations were found for brain ventricles volume, WMHs volume and age.…”
Section: Bootstrap Distribution Of Correlation Between Cardiac Paramesupporting
confidence: 92%
“…Structural and functional left atrial (LA) remodeling is usually a consequence of impaired LV function and elevated LV filling pressure. However, LA remodeling seems to begin at an early stage of LV remodeling or LV diastolic dysfunction 22,23 . Katayama et al showed that increased LV mass index and low Hb concentration was independently associated with LA enlargement in patients with normal LV systolic function 24 .…”
Section: Discussionmentioning
confidence: 99%
“…99 In a recent study from Japan, this LVH-AF link was found to be strongest in those with eccentric and concentric LVH, less so in CR. 100 Accordingly, those with LVH regression by EKG in the LIFE study had a 12% lower rate of new onset AF for every standard deviation reduction in Cornell EKG product. 101 This decreased rate of LVH and new onset AF corresponded with a decreased rate of stroke in the losartan treated arm of this study, further solidifying the relationship between changes in LVM, AF, and stroke.…”
Section: Stroke and Atrial Fibrillation (Af)mentioning
confidence: 90%